The Mechanisms Of Organizing Education In Higher Education Institutions Using The Acmeological Method - R.K. Khaytmetov (Euro Asian Journal Publishing, 2024)
Acmeology, as the science of achieving personal and professional development peaks, holds significant potential for application in higher education. This presentation explores mechanisms for integrating acmeological principles into educational processes within universities, aiming to enhance both student and faculty development. The study employs a mixed-methods approach, analyzing existing literature, conducting surveys with stakeholders, and presenting practical frameworks for implementation. Results demonstrate the method's effectiveness in fostering self-actualization, lifelong learning, and professional excellence. However, challenges such as resource limitations and resistance to change are also highlighted. Recommendations include adopting acmeological-based curricula, targeted faculty training, and continuous evaluation processes. The findings emphasize the transformative potential of acmeology in reshaping higher education
Keywords: Acmeology; Higher Education; Lifelong Learning